2020
DOI: 10.3389/fnagi.2020.00043
|View full text |Cite
|
Sign up to set email alerts
|

“Smelling and Tasting” Parkinson's Disease: Using Senses to Improve the Knowledge of the Disease

Abstract: Among non-motor manifestations of Parkinson's Disease (PD), peripheral, sensory symptoms are particularly relevant. Smell dysfunction starts very early and frequently precedes the PD motor symptoms by years (being often a cue to the diagnosis). Moreover, olfactory system could be, together with gut, one of those peripheral sites where PD pathology first develops. Unlike smell loss, the relationship between PD and taste impairment is far less established. It can start early in the course of the disease but more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 81 publications
2
35
2
Order By: Relevance
“…This specific sensory impairment is also a typical symptom in Parkinson Disease and longitudinal research has shown that olfactory decline is correlated with higher risk in development of the disease ( Haehner et al, 2007 ). Parkinson’s patients report rates of smell impairment in a range between 75 and 95% ( Oppo et al, 2020 ). Olfaction is not exclusively impaired in patients with Parkinson; it is also an early feature of AD and it has been shown to predict progression from mild cognitive impairment (MCI) to AD ( Postuma et al, 2015 ).…”
Section: Entropy In Agingmentioning
confidence: 99%
“…This specific sensory impairment is also a typical symptom in Parkinson Disease and longitudinal research has shown that olfactory decline is correlated with higher risk in development of the disease ( Haehner et al, 2007 ). Parkinson’s patients report rates of smell impairment in a range between 75 and 95% ( Oppo et al, 2020 ). Olfaction is not exclusively impaired in patients with Parkinson; it is also an early feature of AD and it has been shown to predict progression from mild cognitive impairment (MCI) to AD ( Postuma et al, 2015 ).…”
Section: Entropy In Agingmentioning
confidence: 99%
“…Another important issue that also requires careful future analysis is the presence and sustainability of the nervous system damage after the cure of the COVID‐19 infection. This became especially troublesome in light of the fact that the anosmia and ageusia, which are frequently observed among COVID‐19 patients, also serve as characteristic and prodromal nonmotor manifestations of Parkinson's disease (Haehner et al., 2011; Oppo et al., 2020).…”
Section: Sars‐cov‐2 Cellular Entry Receptorsmentioning
confidence: 99%
“…Another important issue that also requires careful future analysis is the presence and sustainability of the nervous system damage after the cure of the COVID-19 infection. This became especially troublesome in light of the fact that the anosmia and ageusia, which are frequently observed among COVID-19 patients, also serve as characteristic and prodromal non-motor manifestations of Parkinson's disease [78,79].…”
Section: Sars-cov-2 Cellular Entry Receptorsmentioning
confidence: 99%